Between adaptation and resistance: Three cases in Huambos colonial (Cajamarca) 1653-1811 - Figueroa Idrogo, Jaisia (2021)
Using the contributions of Steve Stern, Florencia Mallon and other authors, on adaptation, resistance and adaptation in resistance of the peasants to oppression, this article examines -with information from archives- three different cases of social processes in the colonial province of Huambos (Cajamarca), from the awarding of land to original settlers by the Visitor Francisco de Huerta Gutierres (1657) until the end of the 18th century or the beginning of the 19th century. The first case shows an adaptation process; the second reveals a long and successful adaptation in resistance; and the third seems to be a passive adaptation, in which the native peasant who receives land is quickly left aside by settlers and miners.